Drawn to Design : Analyzing Architecture Through Freehand Drawing. - Jenkins, Eric (De Gruyter, 2013)
The book is a guide for students and teachers to understand the need for, the role of and the methods and techniques of freehand analytical sketching in architecture. The presentation focuses on drawing as an approach to and phase of architectural design. The conceptual goal of this approach is to use drawing not as illustration or depiction, but exploration. The first part of the book discusses underlying concepts of freehand sketching in design education and practice as a compliment to digital technologies. The main component is a series of chapters that constitute a typology of fundamental.